2019
DOI: 10.1096/fj.201900322r
|View full text |Cite
|
Sign up to set email alerts
|

Infection‐induced endothelial amyloids impair memory

Abstract: Patients with nosocomial pneumonia exhibit elevated levels of neurotoxic amyloid and tau proteins in the cerebrospinal fluid (CSF). In vitro studies indicate that pulmonary endothelium infected with clinical isolates of either Pseudomonas aeruginosa, Klebsiella pneumoniae, or Staphylococcus aureus produces and releases cytotoxic amyloid and tau proteins. However, the effects of the pulmonary endothelium‐derived amyloid and tau proteins on brain function have not been elucidated. Here, we show that P. aeruginos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(59 citation statements)
references
References 63 publications
4
55
0
Order By: Relevance
“…Supernatant generated following inoculation of PMVECs with DPcrV, a strain that lacks a functional type III secretion system, does not contain secreted cytotoxic Ab and oligomeric tau whereas supernatant produced using strain PA103 does contain the cytotoxic forms ( Fig. 1) [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Supernatant generated following inoculation of PMVECs with DPcrV, a strain that lacks a functional type III secretion system, does not contain secreted cytotoxic Ab and oligomeric tau whereas supernatant produced using strain PA103 does contain the cytotoxic forms ( Fig. 1) [19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we had demonstrated that treatment with a 10‐fold excess of HFIP to PA103 supernatant resulted in loss amyloid epitopes [19]. To assess the effects of HFIP on the structure of endothelial‐derived toxic amyloids at lower ratios of HFIP to supernatant, immunoblot analysis was performed using A11 anti‐amyloid antibody, which we have shown previously recognizes both endothelial‐derived Aβ and oligomeric tau [20,21]. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Like tau, these amyloids demonstrated the ability to propagate in naïve endothelial cells and also displayed some insensitivity to degradation, indicating the behavior of a prion-like entity. In addition to being detected in the bronchoalveolar lavage fluid of patients with P. aeruginosa, they also disrupt long-term potentiation in the rat hippocampus [22,23]. Thus, generation of transmissible and cytotoxic amyloids within the lung may contribute to end-organ dysfunction that is due to ExoY and ExoU.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, recent studies indicate that ExoY is involved in the breakdown of peripheral microtubules and subsequent release of tau and amyloid β. These events lead to decreased endothelial cell barrier integrity and increased end-organ injury in both the pulmonary system and the brain [21][22][23].…”
Section: Introductionmentioning
confidence: 99%